2021
DOI: 10.1111/ddi.13261
|View full text |Cite
|
Sign up to set email alerts
|

Drought, fire and grazing precursors to large‐scale pine forest decline

Abstract: Aim Temperate forests are currently facing multiple stresses due to climate change, biological invasions, habitat fragmentation and fire regime change. How these stressors interact with each other influences how, when and whether ecosystems recover, or whether they adapt or transition to a different ecological state. Because forest recovery or collapse may take longer than a human lifetime, predicting the outcomes of different stressor combinations remains difficult. A clearer vision of future forest trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 113 publications
(195 reference statements)
0
9
0
Order By: Relevance
“…We found that post‐fire herbivory reduced plant species richness, diversity, and evenness and increased plant dominance measures. This was expected as foraging pressure by large herbivores has been shown to decrease diversity and increase species dominance in other ecosystems (Bakker et al, 2006 ; Connor et al, 2021 ; Tuft et al, 2012 ). This finding confirms that increased foraging pressure from large herbivores following a wildfire also results in a more depauperate vegetation community, consistent with previous studies of smaller prescribed/experimental burns (Foster et al, 2015 ; Parkins et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…We found that post‐fire herbivory reduced plant species richness, diversity, and evenness and increased plant dominance measures. This was expected as foraging pressure by large herbivores has been shown to decrease diversity and increase species dominance in other ecosystems (Bakker et al, 2006 ; Connor et al, 2021 ; Tuft et al, 2012 ). This finding confirms that increased foraging pressure from large herbivores following a wildfire also results in a more depauperate vegetation community, consistent with previous studies of smaller prescribed/experimental burns (Foster et al, 2015 ; Parkins et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…Nearby, a few grains were equally found in Mesolithic and Neolithic levels at Lake Racout (French Pyrenees) [ 27 , 28 ]. Secale -type pollen was sporadic in Southwestern Iberia, namely in the sites of Barbaroxa de Baixo (Setúbal) and Lagoa Travessa I (Setúbal), in Neolithic contexts [ 27 , 29 , 30 ]. Numerous palynological studies have been carried out in Northwest Iberia (e.g.…”
Section: Rye In Iberiamentioning
confidence: 99%
“…Secale , Secale -type, and Secale cereale pollen grains are recurrent in Bronze and Iron Age deposits, appearing in more sites and Iberian areas than in the previous periods (e.g. [ 29 , 30 , 37 – 43 ]). Still, the general pattern is identical, with the exception of the record from Chan de Lamoso, which suggests a more consistency of Secale pollen from the Middle Bronze Age onwards, although discontinuous events were equally noted [ 37 ].…”
Section: Rye In Iberiamentioning
confidence: 99%
“…Post‐fire vegetation recovery is influenced by plant functional traits and the prevailing weather conditions (Connor et al, 2021). European beech is an ecologically and economically important forest species in Europe (Prislan et al, 2019; Thiel et al, 2014; Urrutia‐Jalabert et al, 2021), but F. sylvatica contributes also to water and nutrient cycles, influences soil development and habitat structures (Chapin et al, 2002), and plays the role of an ecosystem engineer in many European forests (Azuara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%